MARKETING STRATEGY FOR PAID RICE AGRO-TOURISM IN THE VILLAGE MARKET TRANSFER - Adelina Lubis; Nurul Wardani Lubis; Indah Apriliya; Wimbi Prima Hadi (Jurnal Ekonomi, 2022)
The development of agro-tourism is one alternative that can encourage economic potential in an area. Pasar Melintang Village has the largest expanse of rice fields in Lubuk Pakam, Deli Serdang. Therefore, village rice fields have the potential to be developed into rice field agro-tourism and can become new alternative tourist destinations in Deli Serdang Regency and its surroundings. This research aims to formulate an environmentally friendly agro-tourism marketing strategy in Pasar Melintang Village. This qualitative descriptive study uses SWOT analysis to formulate a marketing strategy for rice field agrotourism in Pasar Melintang Village. Partners in this study were 21 people from Mulia farmer groups, community leaders, and related institutions. The result of this research is the need for a diversification strategy to minimize obstacles by maximizing the village's strengths. Then there are five alternative ST (Strength-Threat) strategies that can be used in developing village rice fields.